(untitled) (GYMNASIUM, 2011)
Mentality and the requirement of the sport today has a clear trend of finding new solutions to enhance the capacity of the human performance test regardless of branch or practiced. One of the goals it needs to meet current systemic concept of sports training in which training has three parts (motor, physiological and psychological) that are found in standing balance and interdependence.